Impact of microsporidian infection on growth and development of silkworm Bombyx mori L. (Lepidoptera: Bombycidae) - Gupta, Sunil Kumar; Hossain, Zakir; Nanu, Madana Mohanan; Mondal, Kalidas (Agriculture and Natural Resources, 2016)
Several species and strains of microsporidia have been isolated from infected silkworms among which pebrine caused by Nosema bombycis Nageli is the most important. Infection from this disease causes severe economic loss in sericulture. Reduction of larval and pupal development and reduced weights in silkworms due to infection has been reported. In the present study, five microsporidian (Nosema) isolates from mulberry silkworm, Bombyx mori L. collected from different locations in West Bengal, India were sampled to study the impact of their infection on the growth and development of B. mori. The study revealed significant differences among the isolates in their ability to cause a reduction in the larval and pupal development of silkworm. Healthy larvae showed better body and tissue weights which were significantly higher than in infected lots. Among the isolates, M5 registered the maximum reduction in relative growth rate, larval silk gland tissue somatic index, larval male and female gonad tissue somatic index (GTSI) and pupal female GTSI compared to the healthy control. Male and female pupa treated with M5 spores died before emergence, suggesting that the M5 isolate was the most virulent.